NEOLIBERALISMO E LUTAS SOCIAIS NA BOLÍVIA: da guerra da água à guerra do gás (2003-2005) - Castro Júnior, Raimundo Campos (2014)
This dissertation discusses the social struggles in Bolivia, during the Water War and the Gas War, in a context of widespread social unrest. We seek to understand the social context of the country, from the neoliberal economic restructuring. We present a socio-historical approach to reveal the social actors involved: their desires, their contradictions; the development of the struggle of the exploited class organizations and the process of struggle and resistance that invigorates an anti-imperialist nationalism imprint. Include the emergence and political-ideological structure of the main organizations who participated in the overthrow of two presidents in the timeline pertaining to this work, especially the proletariat of El Alto and the coca growers, who developed a fight to defend their ethnic-cultural values attached to their demands classist. The study is based on a historical-materialist approach, which inserts Bolivia in a context of global imperialist domination and how the struggle for nationalization of natural resources of the country, led by the exploited classes, could open a new cycle of social struggles, resulting in profound socio-political changes, from this process.